Pulsed Nd:YAG laser welding of UNS S 32205 duplex stainless steel - Crespo, Gillian da S. [UNESP]; Padilha, Josiel L. [UNESP]; Sokei, Celso R. [UNESP]; Tokimatsu, Ruis C. [UNESP]; Gallego, Juno [UNESP]; Ventrella, Vicente A. [UNESP] (Trans Tech Publications, 2016)
This paper reports an experimental study of laser welding on duplex stainless steel UNS S32205 employed in the oil and natural gas industries. A pulsed Nd:YAG laser was used to weld the specimens. Bead on plate condition was used. Scanning Electron and Optical microscopy was applied to measure and analyze the cross-sectional of the weld bead. From the experimental results, it was found that the shape and size of the welded spot depend not only on the laser energy, but also on the pulse duration and the focus position. Metallographic observations showed that the microstructure of the weld metal was characterized by large ferrite grains with intra and intergranular austenite. Large voids delimited by the molten zone boundary were observed in weld beads with low pulse duration. The heat affected zone resulting from the welding is pretty much absent and no cracks were detected.
Keywords: Duplex steel; Nd:YAG; Pulsed laser; UNS S32205; Welding